Nocturnal Blood Pressure Pattern Affects Left Ventricular Remodeling and Late Gadolinium Enhancement in Patients with Hypertension and Left Ventricular Hypertrophy - Yokota, Hajime (Public Library of Science, 2013)
BACKGROUND: Left ventricular hypertrophy (LVH) is an independent predictor of cardiac mortality, regardless of its etiology. Previous studies have shown that high nocturnal blood pressure (BP) affects LV geometry in hypertensive patients. It has been suggested that continuous pressure overload affects the development of LVH, but it is unknown whether persistent pressure influences myocardial fibrosis or whether the etiology of LVH is associated with myocardial fibrosis. Comprehensive cardiac magnetic resonance (CMR) including the late gadolinium enhancement (LGE) technique can evaluate both the severity of changes in LV geometry and myocardial fibrosis. We tested the hypothesis that the nocturnal non-dipper BP pattern causes LV remodeling and fibrosis in patients with hypertension and LVH. METHODS: Forty-seven hypertensive patients with LVH evaluated by echocardiography (29 men, age 73.0±10.4 years) were examined by comprehensive CMR and 24-h ambulatory blood pressure monitoring (ABPM). RESULTS AND CONCLUSIONS: Among the 47 patients, twenty-four had nocturnal non-dipper BP patterns. Patients with nocturnal non-dipper BP patterns had larger LV masses and scar volumes independent of etiologies than those in patients with dipper BP patterns (p = 0.035 and p = 0.015, respectively). There was no significant difference in mean 24-h systolic BP between patients with and without nocturnal dipper BP patterns (p = 0.367). Among hypertensive patients with LVH, the nocturnal non-dipper blood pressure pattern is associated with both LV remodeling and myocardial fibrosis independent of LVH etiology.